PWE-109 Bleeding the bronze diabetics:prospective audit against local, national and european guidelines of venesection in hereditary haemochromatosis at a district general hospital in scotland. (22nd June 2015) - Johnston, M; El Nujumi, A
Abstract : Introduction: Patients with haemochromatosis and evidence of iron excess should be treated with venesection. This confers a normal life expectancy in the absence of cirrhosis and diabetes. Over 400 patients regularly attend Wishaw for venesection. We aimed to document haemoglobin and ferritin; and whether venesection is done based on these results. We additionally checked genotype. Method: Prospective audit of all gastroenterology patients with hereditary haemochromatosis attending for venesection over 7 weeks. Results compared against local, BCSH and EASL guidelines. Results: There were 61 attendances by 41 patients. Ferritin was regularly checked but 6 patients were venesected despite already achieving the target (<50 μg/L). 6 patients did not have haemoglobin checked before venesection. 8 patients were venesected despite low haemoglobin. 25 of 41 patients had been genotyped. Liver biopsy had been performed in only 2 of 11 patients in whom it was indicated. Conclusion: There is scope to improve safe venesection based on ferritin and haemoglobin. There was variation in how aggressively patients were venesected in clinic. One contributing factor is thought to be the differing target values used by haematologists and gastroenterologists in the hospital. In an attempt to address this the venesection protocol is to be standardised across patients. This is a popular change with venesection clinic staff. Another factor is that patients' individual venesection booklets do not follow their case notes to clinic appointments. This would allow clinicians to monitor patients' venesection more actively. Disclosure of interest: None Declared.